PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP MOTIVASI DAN BERPIKIR KRITIS SISWA - Sayyidah Hanim Ahida Suci; Rusijono Rusijono; Muhammad Jacky (JURNAL TEMATIK, 2021)
This study aims to determine the effect of applying contextual learning on students’ learning motivation and critical thinking. The subjects of this study were 5th grade students of Muhammadiyah elementary school 2 Tulangan Sidoarjo with Social Sciences subjects on the geographical characteristics of Indonesia. The research method used was a quasi-experimental research (quasi-experiment) with a pretest and post-test control group design. The data collection technique was done by random samping, namely class 5A as the experimental group and class 5B as the coontrol group. The instruments used include observation sheets, motivasion questionnaires, and pretest-post-test questions. Data were analyzed by independent t test. The results of this study were that the application of contextual learning has an effect on increasing learning motivation for the experimental group with an average of 36.27 and the control group with an average of 36.23. It also improved critical thinking with an average of 97.23 in the experimental group and an average of 94.83 in the control group. Through the independent t test, a significance value of 0.000 > 0.05 was been obtained. Thus, the application of contextual learning could significantly affect the learning motivation and critical thinking of fifth grade students of Muhammadiyah elementary school 2 Tulangan Sidoarjo.